THE THIRD ORDER IN THE UNDERGROUND: LAY ORGANIZATIONS OF THE UKRAINIAN GREEK CATHOLIC CHURCH IN PRECARPATHIAN REGION IN THE 1970S-1980S - Oleg Zhernokleyev (Vasyl Stefanyk Precarpathian National University, 2015)
The paper highlights the role of communities of monks and nuns (the Third Orders) in the structure and activity of the Ukrainian Greek Catholic Church (UGCC), which functioned underground. It is emphasized that the historical roots of the Third Order are traced back to the 13th century when spiritual life of specific lay communities was regulated by the Franciscan and the Dominican Orders, and later, by the Carmelite Order. Between 1900 and 1930s lay communities of the UGCC became noticeably active. A characteristic example of their activity is the well known Rules for laypersons of the Basilian Order drawn by Metropolitan Archbishop Andrey Sheptytsky. In the 1970s (the Soviet time, when the UGCC worked underground), there appeared the Redemptorist and the Basilian Third Orders in Ivano-Frankivsk Oblast. Their members kept in safety different cult objects, held underground Divine Services, meetings, had spiritual practices, did catechesis, etc. On the whole, these lay communities had played an important role in the UGCC underground activity up till the late 1980s.